Constructive controversy and creative process engagement: The roles of positive conflict value, cognitive flexibility, and psychological safety. Issue 2 (17th January 2018) - Ou, Zhanying; Chen, Tingting; Li, Fuli; Tang, Pokman
Abstract: This research explores how and when constructive controversy enhances creative process engagement. We identify positive conflict value and cognitive flexibility as two mediating processes that transmit the effect of constructive controversy on creative process engagement. We further theorize that psychological safety shows opposing moderating effects: It strengthens the positive conflict value–creative process engagement link, whereas weakens the cognitive flexibility–creative process engagement link. Moreover, we propose that psychological safety strengthens and weakens the two mediating pathways through positive conflict value and cognitive flexibility, respectively. Results based on a multiwave data involving 239 employees from the research and development division of a large high‐technology company provide support for our hypotheses. Theoretical and practical implications are discussed.